R&D key to make Malaysia Asean logistics services hub - M. Ali, Sharidan (The Star, 2014)
SHAH ALAM: Malaysia has to leverage on its strength to ramp up its logistics services sector with more tools and services via research and development (R&D) towards becoming Asean's next logistics hub, said Northern Corridor Implementation Authority chief executive Datuk Redza Rafiq.